ENGKLEK SEBAGAI SARANA PEMBELAJARAN YANG ASIK DI TENGAH PERMAINAN MODERN - Pebryawan, Krisna (MAGISTRA, 2015)
Engklek game is a type of traditional childrenâs games are quite popular in his time. engklekbecome the most widely played game, the many variants, both the name and form. In this paper we study aboutthe importance of maintaining engklek game in the middle of the rapids game paced modern luxury. Engklekgame is not meant to get rid of the modern game, not antipathy to the modern game. The game is intended as acounterweight engklek between the modern game and traditional games. The analysis in this paper includesthe values contained in the game engklek seen from the pattern drawing and playing techniques. The expectedresult is the kids have fun in the play engklek especially able to absorb the values contained in the gameengklek like sportivity, hard work, creativity, and sense of community